Does Economic Growth Responses to Changes in Financing Policies? Signals from Sudan Economy (1997-2018) - Mustafa, Omer Allagabo Omer Mustafa (Archives of Business Research, 2020)
Through a simple regression model, the study tries to examine whether the economic growth in Sudan responses to changes in financing policies adopted by the Central Bank of Sudan(CBOS) during the period (1997-2018. Gross Domestic Product growth rate was used to measures economic growth (The dependent variable). While flow of banking finance to economic sectors includes; Agriculture, Industry, Local Trade, Foreign Trade, Transport and Storage, Energy and Mining and Real Estate were used to indicates changes in financing policies (The independent variables). Data were collected from annual reports of the CBOS. The results reveal that economic growth significantly responses to changes in financing policies but with different degrees during the period of the study. Moreover, it is found that imbalanced economic growth is directly related to imbalanced distribution of finance to economic sectors. The study strongly recommends that, the monetary authority should be issuing financing policies lead to equitable distribution of banking finance among economic sectors in order to achieve sustainable and balanced economic growth.